Estudo da fadiga de duas misturas de solo-cimento - Concha, Luis Marcial Collarte (1986)
This research work deals with repeated-load for flexural test and indirect tensile test, for two differents tipes of soil-cement: lateritic soil-cement mixture and saprolitic soil-cement mixture. Fatigue curves, in terms of stress, strain and stress level, were developed for the two stabilized materials, of each repeated load-test. A comparision was made, of the effects in resistence and fatigue’s life, between flexural test and indirect tensile test, and between lateritic soil-cement mixture and saprolitic soil-cement mixture. The results of this investigation were applied to a computational simulation, to represent the structural behaviour of a paviment with a soil-cement base. Finally, comments and suggestions are made to improve the knowledge of soil-cement mixtures made with saprolitic or lateric soil.